Antitumor Activity of an Anti-EGFR/HER2 Bispecific Antibody in a Mouse Xenograft Model of Canine Osteosarcoma - Nami Tateyama; Hiroyuki Suzuki; Tomokazu Ohishi; Teizo Asano; Tomohiro Tanaka; Takuya Mizuno; Takeo Yoshikawa; Manabu Kawada; Mika K. Kaneko; Yukinari Kato (MDPI AG, 2022)
The overexpression of epidermal growth factor receptors (EGFRs) has been reported in various human tumors, including breast, gastric, lung, colorectal, and pancreatic cancers. Humanized anti-EGFR and anti-human epidermal growth factor receptor 2 (HER2) monoclonal antibodies (mAbs) have been shown to improve patients' survival. Canine tumors resemble human tumors in the initiation and progression. We previously established a defucosylated mouse-dog chimeric anti-EGFR mAb (E134Bf) and a mouse-dog chimeric anti-HER2 mAb (H77Bf), which exerted antitumor activities in canine tumor xenograft models. Here, we produced E134Bf antibody fused to H77Bf single chain Fv at the light chains (E134Bf-H77scFv). The bispecific E134Bf-H77scFv recognized dog EGFR (dEGFR) and dog HER2 (dHER2)-overexpressed Chinese hamster ovary-K1 cells by flow cytometry. E134Bf-H77scFv also reacted with dEGFR/dHER2-positive canine osteosarcoma D-17 cells, and possesses a high binding-affinity (KD: 1.3 × 10−9 M). Furthermore, E134Bf-H77scFv exerted antibody-dependent cellular cytotoxicity and complement-dependent cytotoxicity against D-17 cells in the presence of canine mononuclear cells and complement, respectively. Moreover, administration of E134Bf-H77scFv suppressed the development of D-17 xenograft tumor in mice early compared with the control dog IgG, E134Bf and H77Bf alone. These results indicate that E134Bf-H77scFv exerts antitumor activities against dEGFR/dHER2-positive canine tumors, and could be a valuable treatment regimen for canine tumors.